West Java Economy: Cirata Floating Solar Investment Impact, Input Output Analysis - Rizky, Putri Aulia; Salim, Agus; Suharto, Umayatu Suiroh (Universitas Gorontalo, 2025)
Cirata Floating Solar Power Plant (PLTS) is one of the largest floating solar power plants in Southeast Asia. This infrastructure development aims to provide electricity supply located in Cirata reservoir, West Java province. This study identifies the impact of the Cirata Floating Solar Power Plant development in 2023 on economic conditions in West Java province. The use of this analysis can identify the economic impact of the linkages between sectors in West Java Province. The main data used in the research is the Input-Output (IO) Table of West Java Province Domestic Transactions at Producer Prices (52 Industries), 2016 (Million Rupiah). The analysis method used in this research is general equilibrium. The results of the analysis explain that there is an impact of investment in the construction of Cirata Floating Solar Power Plant on changes in output, compensation of labor and business surplus in the oil, gas and geothermal mining industry, the electricity industry and the gas procurement and ice production industry in West Java Province.